The heterogeneous association between education and the adoption of safe food handling practices in Ethiopia - Su, K.; Kowalcyk, B.; LaPolt, D.; Gazu, Lina; Alonso, Silvia; Azmeraye, B.M.; Degefaw, D.; Mamo, G.; Angaw, D.A.; Teshale, A.M.; Scharff, R. (Springer, 2025)
Background: Foodborne disease is a great concern to low- and middle-income countries. To prevent illness and death, intervention strategies need to be implemented across the food safety system and should include promoting the adoption of safe food handling practices. The positive association between education and health has been well-established, and one possible mechanism is that education may improve health by encouraging individuals to adopt more appropriate protective practices. Decisions regarding adoption of these practices may also be influenced by the food safety risks individuals face, the trade-offs they make to maximize utility, or behavior biases which may be correlated with education. This study aims to estimate the heterogeneous association between education and the adoption of safe food handling practices among people facing different levels of food safety risk.